Adição de espécies radicalares a azometinas iminas e nitronas: síntese e aplicação de c-glicosil pirazolidinona e obtenção de aminas via LMCT - Gonçalves, Renan de Oliveira (2025)
Nitrogen compounds play a central role in several areas of applied chemistry, being present in agrochemicals, pharmaceuticals, food additives, and polymeric materials. Among the modern strategies for obtaining and modifying these structures, methodologies based on photocatalysis stand out, allowing the selective generation of radicals under visible light. In this context, this thesis describes the development of innovative synthetic approaches for the functionalization of nitrogenous species such as azomethine imines and nitrones, exploiting their capacity as nucleophilic radical acceptors in photoinduced reactions. In Project 1, a metal-free photocatalytic methodology was developed for the non-anomeric C-glycosylation of azomethine imines, using 4-glycosyl-1,4-dihydropyridines (DHPs) as radicais precursors and 4CzIPN as a photocatalyst in acetonitrile. The protocol resulted in the development of a new class of C-glycosyl pyrazolidinones under mild conditions, with broad scope and scalability. The derivatives obtained were subsequently modified, including acylation, acetonide deprotection, and reduction, demonstrating the synthetic potential of the methodology. Furthermore, the C-glycosylation methodology was adapted to continuous flow systems, enabling the efficient synthesis of a library of 30 compounds with greater savings in time, reagents, and solvents. The products obtained were subjected to antiplasmodial activity assays in collaboration with CIBFar-USP. Sixteen compounds demonstrated significant activity (IC50 < 10 µM) with low cytotoxicity and good selectivity. Structure-activity relationship analysis revealed that the presence of a phenyl at position 5 of the pyrazolidinone and the glycosidic moiety are determinants of bioactivity, consolidating these units as promising pharmacophoric fragments against Plasmodium falciparum. In Project 2, a novel strategy was developed for the alkylation of nitrones and subsequent reduction of hydroxylamine to amines using ligand-to-metal charge transfer (LMCT) catalysis with Fe(III) under visible light. The methodology employs carboxylic acids as a source of alkyl radicals and initially generates hydroxylamines in situ, which are reduced to amines without the use of stoichiometric metal reducing agents. Overall, the results obtained throughout this thesis demonstrate the potential of photochemical approaches in the development of sustainable and efficient methodologies for the selective functionalization of nitrogenous systems, in addition to contributing new perspectives for the discovery of bioactive compounds.